The Effect of Ethnomathematics E-Modules in Problem-Based Learning on Elementary Students Mathematics Learning Outcomes - Eko Pujianto; Seprie Seprie (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
This study aims to examine the effect of the Problem Based Learning (PBL) model assisted by ethnomathematics-based e-modules on elementary students’ mathematics learning outcomes on geometry topics. A quantitative approach with a quasi-experimental nonequivalent control group design was applied. The experimental group received PBL instruction supported by ethnomathematics-based e-modules, while the control group received conventional instruction. Data were collected using a 20-item multiple-choice test with validated reliability (Cronbach’s alpha). Data analysis included normality and homogeneity tests, an independent sample t-test, and N-gain analysis. The results showed a independent t-test indicated a significant effect (t = 5.12, p < 0.001). The experimental group achieved a higher N-gain score (0.62, medium to high category) compared to the control group (0.36, medium category). These results indicate that PBL assisted by ethnomathematics-based e-modules significantly improves students’ mathematics learning outcomes. The findings highlight the effectiveness of integrating contextual learning models and digital ethnomathematics media in improving learning achievement in elementary mathematics education.